The ECB monetary policy strategy and the money market - Vítor Gaspar; Gabriel Perez-Quiros; Jorge Sicilia (Oesterreichische Nationalbank (OeNB), 2001)
This paper aims at contributing to the understanding of how the ECB conducts monetary policy as seen from a money market perspective. More specifically it covers two different issues. First, it looks at the learning period for banks since the Eurosystem started implementing the single monetary policy. It shows that during the first three weeks of 1999 the narrow corridor in place during this period was effective in limiting daily volatility of the money market overnight rates. In addition, the behaviour of banks and market rates during this period provides evidence that learning was taking place. Second, it looks at how well money market participants have anticipated the monetary policy decisions taken by the ECB. To do so, the paper analyses whether the announcements of monetary policy decisions to maintain or change interest rates impact on the stochastic behaviour of interest rates. Looking at the EONIA rates within the reserve maintenance periods, we find that the announcement of monetary policy decisions does not change significantly the level or volatility of overnight rates.
Keywords: 330